2018
DOI: 10.1017/s0144686x18000119
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, limb-loss and military veterans: a systematic review of the literature

Abstract: The impact of losing a limb in military service extends well beyond initial recovery and rehabilitation, with long-term consequences and challenges requiring health-care commitments across the lifecourse. This paper presents a systematic review of the current state of knowledge regarding the long-term impact of ageing and limb-loss in military veterans. Key databases were systematically searched including: ASSIA, CINAHL, Cochrane Library, Medline, Web of Science, PsycArticles/PsychInfo, ProQuest Psychology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Indeed, the phrase resonates strongly with Ledwidge's (2011) description of the Army's 'cracking on' mentality; a relentlessly positive, forwardlooking approach that may be defined as "getting on with whatever is at hand with enthusiasm" (p. 144). Tellingly, the veterans in this study continued to embody the 'get on with it' approach to remain active despite experiencing limited physical mobility, and to withstand various forms of pain and comorbidities (see Caddick et al, 2018;Williams et al, 2017). The approach highlights both the lifelong legacy of military ways of being (Caddick et al, 2015;de Medeiros & Rubenstein, 2016), and the continuity of traditional ideals of masculinity in the lives of older men more generally (Thompson & Langendoerfer, 2016).…”
Section: Stories Of Limb-lossmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, the phrase resonates strongly with Ledwidge's (2011) description of the Army's 'cracking on' mentality; a relentlessly positive, forwardlooking approach that may be defined as "getting on with whatever is at hand with enthusiasm" (p. 144). Tellingly, the veterans in this study continued to embody the 'get on with it' approach to remain active despite experiencing limited physical mobility, and to withstand various forms of pain and comorbidities (see Caddick et al, 2018;Williams et al, 2017). The approach highlights both the lifelong legacy of military ways of being (Caddick et al, 2015;de Medeiros & Rubenstein, 2016), and the continuity of traditional ideals of masculinity in the lives of older men more generally (Thompson & Langendoerfer, 2016).…”
Section: Stories Of Limb-lossmentioning
confidence: 97%
“…Yet, as Settersten (2006) argued, there is often a lifelong legacy of military service with significant implications for physical, mental, and social functioning in later life. This legacy is most visible in physical wounds such as limb amputations that some military personnel experience through service, and the long-term after effects of these injuries (see Caddick et al, 2018). As Cooper et al, (2018) argued, however, military experience also exerts a more subtle enduring legacy on the identity and behaviour of veterans, shaping how they respond to challenges in civilian life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Epidemiological studies indicate that up to 95% of patients report post-amputation pain 10 and 85% reported significant pain even decades after amputation. 8 Although PLP and RLP are most commonly reported in the literature, with noted incidence rates of 50%-80%, [11][12][13][14] there is ample evidence that pain in other body sites also is a prominent problem for amputees. Mazzone et al 12 recently found that 49% of amputees experience recurrent back pain, while Esfandiari et al reported a staggering 69% of patients reported chronic back pain.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of losing a limb extends well beyond initial recovery and rehabilitation, with long-term consequences and challenges requiring health and social care commitments across the life-course [2]. Existing literature highlights that veterans who have experienced limb loss are, for the most part, able to achieve and maintain good quality of life [3]. Nevertheless, the amputation of a limb, or limbs, is a progressive injury.…”
Section: Introductionmentioning
confidence: 99%